Studies of plasma confinement in GOL-3 multi mirror trap - Arzhannikov, A.; Astrelin, V.; Beklemishev, A.; Burdakov, A.; Burmasov, V.; Derevyankin, G.; Ivanenko, V.; Ivanov, I.; Ivantsivsky, M.; Kandaurov, I.; Konyukhov, V.; Kotelnikov, I.; et al. (Вопросы атомной науки и техники, 2006)
Recent results of the experiments at GOL-3 facility are presented. Plasma with a density of 10¹⁴…10¹⁶ cm⁻³ is confined in a 12-meter-long solenoid, which comprises 55 corrugation cells with mirror ratio Bmax/Bmin=4.8/3.2 T. The plasma is heated up to 2…4 keV temperature by a high power relativistic electron beam (~1 MeV, ~30 kA, ~8 µs, ~120 kJ) injected through one of the ends. Mechanism of experimentally observed fast ion heating, issues of plasma stability and confinement are discussed. Представлены недавние результаты экспериментов на установке ГОЛ-3. Плазма с плотностью 10¹⁴…10¹⁶ см⁻³ удерживается в 12-метровом соленоиде, состоящем из 55 ячеек с пробочным отношением Bmax/Bmin=4.8/3.2 Тл. Плазма нагревается мощным релятивистским электронным пучком (~1 МэВ, ~30 кА, ~8 мкс, ~120 кДж) до температуры 2…4 кэВ. Обсуждаются механизм быстрого нагрева ионов, вопросы устойчивости и удержания плазмы. Представлено недавні результати експериментів на установці ГОЛ-3. Плазма з густиною 10¹⁴…10¹⁶ см⁻³ утримується в 12-метровому соленоїді, який складається з 55 осередків із пробковим відношенням Bmax/Bmin=4.8/3.2Тл. Плазма нагрівається могутнім релятивістським електронним пучком (~1 МеВ, ~30 кА, ~8 мкс, ~120 кДж) до температури 2...4 кеВ. Обговорюються механізм швидкого нагрівання іонів, питання стійкості й утримання плазми.